Risk Factors of Antituberculosis Induced-Hepatotoxicity amongHIV/AIDS Patients - Luthariana, Lies; Karjadi, Teguh H.; Hasan, Irsan; Rumende, C. Martin (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Antituberculosis (ATT) induced hepatotoxicity is commonly found among HIV/AIDS patients. Several risk factor related to drug-induced hepatotoxicity such as alcoholism, hepatitis B or hepatitis C infection, abnormal baseline aminotransferase/bilirubin, poor nutritional status and concomitant hepatotoxic drugs consumption, are usually found in these patients. This study was conducted to evaluate risk factor of ATT-induced hepatotoxicity in HIV/AIDS patients. Methods. This is a case control retrospective study with matching of age, sex, antituberculosis regimen, and alcohol consumption. Risk factors evaluated are hepatitis C and hepatitis B coinfection, concomitant hepatotoxic drugs consumption, abnormal baseline aminotransferase and or bilirubin. Results. We collected data of 33 cases and 33 controls We found 82% subjects in case group and 76% subjects in control group have hepatitis C coinfection; 18% subjects in case group and 6% subjects in control group have hepatitis B coinfection. Fifty four point five percent (54.5%) subjects in case group and 42.4% subjects in control group consume other hepatotoxic drugs. Elevated baseline ALT level was found in 51.5% subjects in case group and 12% subject in control group. Bivariate analysis showed that the risk of hepatotoxicity was higher in patients with elevated baseline ALT level (OR=7.5; 95% CI 1,72- 32,80; p < 0,05). Conclusions. Elevated baseline ALT level will increase antituberculosis drug induce hepatotoxicity risk up to 7.5 times. There were no association between hepatitis C, hepatitis B, concomitant hepatotoxic drugs consumption and antituberculosis drug-induced hepatotoxicity in HIV/AIDS patients.